Community Empowerment Based on Religious Groups “JSN Cengkir Gading” - Khoirul Rahman; Kevin Kurnia Gumilang (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
Most religious groups only focus on religious activities and do not touch on other aspects of life. JSN Cengkir Gading in addition to carrying out the function of the "dakwah" of Islam to its congregation also conducts community development programs with the concept of “ekonomi kerakyatan”. So it is interesting to see whether religious-based groups are effective in the implementation of community empowerment. This paper uses descriptive qualitative methods to facilitate the writer in exploring this social phenomenon, then it will be described descriptively by providing a detailed picture and explanation so that the results are presented easy to understand. In the context of JSN Cengkir Gading empowerment is carried out by utilizing the potential of the region possessed and carried out in accordance with Islamic guidelines. The correlation between efforts to increase religiosity through religious activities, and productivity through the empowerment program has directly improved the economy of the community so that the empowerment of religious group-based communities in JSN Cengkir Gading is considered effective.